Analysis of the misuse of customer-friendly returns services in e-commerce by ultimate consumers (B2C) - Mona Sonntag (Journal of Applied Leadership and Management, 2019)
Research question: The present paper deals with the question of which consumers take advantage of the customer-friendly returns service and whether consumers are aware of the consequences of account blocking. Against the background of this question, it is of interest whether abuses are more likely to be committed by consumers who additionally cause many returns, or whether there is no discernible difference. Methods: A quantitative research in the form of an online survey is conducted to collect the data that is subsequently evaluated in order to obtain meaningful results. The participants are internet buyers who complete the questionnaire generated for the survey online. Results: It was possible to prove connections between the frequency of returns, and the preference to order online. It was found that consumers who take advantage of the returns service usually have higher return rates. Furthermore, in the consequence of user account blocking, it could be demonstrated that the group of consumers with experience in this regard reported higher returns than the other group.
Keywords: 650